Peers-for-peers (P4P): an efficient and reliable fault-tolerance strategy for cycle-stealing P2P applications. (11th February 2011) - Gupta, Ankur; Awasthi, Lalit K.
Cycle-stealing P2P applications need to contend with a transient node population, which requires specialised approaches to be formulated to achieve fault-tolerance. This research paper proposes the peers-for-peers (P4P), an efficient and reliable strategy, based on selecting suitable peers to provide fault-tolerance for P2P applications by redundantly storing check-pointing or message logging data, ensuring its survivability. The strategy is suitable for cycle-stealing P2P applications and is optimised to reduce the message exchange overheads compared to other existing approaches, while alleviating the need to retrieve/reconstruct check-pointing data thereby improving application performance. Simulation results establish the effectiveness of the strategy in choosing quality nodes which meet the application computing requirements and ensuring survivability of check-pointing data in the face of heavy node transience. A real-world implementation based on the JXTA framework establishes its applicability to cycle-stealing P2P applications.